Enhanced Adaptive Overcurrent Protection Scheme for AC Microgrid and Its Real-Time Validation Through Cyber Physical Power System Testbed - Jagan A.; Prasad U.; Mohanty S.; Singh S. (My University, 2025)
This paper introduces a Relay Integrity and Anomaly Detection (RIAD) scheme designed to enhance the reliability of Setting Group-based Adaptive Overcurrent (SGAO) protection systems. The RIAD mechanism improves relay configuration awareness and mitigates potential failures due to misconfigured relays or cyber intrusions targeting relay settings. To validate the performance of SGAO and the proposed RIAD, a comprehensive cyber-physical power system testbed was developed and implemented within the CIGRE 7-bus AC microgrid. This field-level testbed, featuring IEC 61850-based Hardware-in-the-Loop (HIL) experimentation with Real-time Digital Simulation (RTDS) and industry-grade relays such as SEL 421, 751, and 311C, along with an automation controller (SEL RTAC 3530-4) for logic implementation, provides a precise timeline analysis of events. The testbed highlights the significance of validating enhanced SGAO schemes under real-world conditions, ensuring robust relay settings and coordination even in the presence of communication failures, misconfigurations, or cyber-attacks. © 2025 John Wiley & Sons Ltd.